Aesthetic criticism of dancers' costumes at Jaranan Pegon's performance in Trenggalek - Mellany Octa Salsabila Sugiarto; I Nengah Mariasa; Setyo Yanuartuti (Pascasarjana Institut Seni Indonesia Surakarta, 2023)
Aesthetic criticism serves as an evaluation of diverse forms of beauty perceived differently by individuals. Costumes worn by Jaranan Pegon dancers adhere to specific standards and regulations during performances, with the dancers donning Wayang Wong attire. This research aims to assess aesthetic criticism by investigating absolutism, anarchy, and relativism in the costumes of Jaranan Pegon dancers. The study employed a descriptive approach with a phenomenological method. The findings revealed that, in accordance with absolutism, Jaranan Pegon dancers' costumes must adhere to established standards or guidelines. From the perspective of anarchy, there is freedom in costume choices, allowing deviation from traditional rules. Relativism permits flexibility in attire, considering various presentation factors while still allowing departures from established guidelines. The significance of this research lies in exploring aesthetic criticism through the lenses of absolutism, anarchy, and relativism in the context of Jaranan Pegon dancers' costumes, shedding light on the varying standards and freedoms associated with costume choices in performances.